POLITISASI BIROKRASI DI INDONESIA - RINA MARTINI, RINA MARTINI (Program Magister Ilmu Politik, Universitas Diponegoro, 2010)
AbstractIndonesian bureaucracy is built in a long history, since an era of kingdom until an era of thestate formation called Indonesia. However, the characteristics of the bureacracy is mainly identifiedas patrimonialistic. The characteristics are inheritted until in the era of reformation when politicalstructure has been reconstructed to be more democratic. The efforst to reform seem not to yield amore legal-rationalistic typology of bureacracy. One of the reasons is a highly politicized bureaucracyin the forms of for example the uses of public facilities for particular political partties’ activities, politicalmobilisation in general election, the practices of spoil system in bureaucracy, political interest-basedpromotion for public officers, government officer recruitment, and the dismantle of career officers ofgovernment institution that is highly political. However, it is not easy to eradicate the politicization ofbureacracy since both of them are closely linked. Ideally, the links between bureacracy and politicsmust be oriented for accommodating public interests.Key word : bureaucracy, politics, politicized bureaucra